Unconventional calibration strategies for micromanipulation work-cells. Issue 12 (20th August 2018) - Fontana, G.; Ruggeri, S.; Legnani, G.; Fassi, I.
SUMMARY: This paper presents and compares a set of calibration strategies useful to calibrate vision-based robotised work-cells for micromanipulation and microassembly. To grasp and release microparts precisely, robot calibration, camera calibration and robot-camera registration are needed. Conventional calibration methods are very onerous at the microscale, therefore, two alternative unconventional procedures, called virtual grid calibration and hybrid calibration, are developed for work-cells with high-performance robots, minimising necessary instrumentation. Moreover, an effective calibration of the robot end-effector is designed to compensate for misalignment and orientation errors with respect to the vertical rotational axis. This paper describes the calibration methods and their implementation, the results and the improvements achieved. A detailed comparison between the hybrid and the virtual grid calibrations is provided, demonstrating the higher performance of the latter strategy.